2009
DOI: 10.1080/07908310903075159
|View full text |Cite
|
Sign up to set email alerts
|

English-only language-in-education policy in multilingual classrooms in Ghana

Abstract: This paper, based on the findings of a qualitative study, discusses the influence of Ghana's recently introduced English-only language-in-education policy on pupils' classroom communicative practices and learning generally. It highlights how the use of English -an unfamiliar language -creates anxiety among students and stalls effective classroom participation. The paper first considers the key issues that impinge on the literacy development in multilingual classrooms in postcolonial Africa including the uninfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…In regard to this question, I find coherence between this study and what Magogwe (2007) found in Botswana. Earlier research (Brock-Utne, 1997;Opoku-Amankwa, 2009;Spernes, 2011) indicates that there is agreement between politicians, parents and teachers regarding language as a medium of instruction in school. They prefer English to be the language used in school, especially because of its relationship to students' outcome.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In regard to this question, I find coherence between this study and what Magogwe (2007) found in Botswana. Earlier research (Brock-Utne, 1997;Opoku-Amankwa, 2009;Spernes, 2011) indicates that there is agreement between politicians, parents and teachers regarding language as a medium of instruction in school. They prefer English to be the language used in school, especially because of its relationship to students' outcome.…”
Section: Discussionmentioning
confidence: 93%
“…Passivity may also have arisen as a consequence of tedious lectures or a combination of tedium and a lack of English proficiency. Based on my interpretation of the atmosphere in the classroom, I have no reason to believe that the students in standard eight felt frustrated, apprehensive or tense (Lunga, 2004;Opoku-Amankwa, 2009). In the focus groups, all the students were surprised when they were told that they were free to speak whatever languages they wanted -English, Swahili or Nandi.…”
Section: English and Swahili Are Better In Schoolmentioning
confidence: 97%
“…The type of questions teachers pose often requires only a short answer, but teachers' choice of questions may be affected by the level of French of the pupils in the classroom. Indeed, this interpretation is supported by some researchers who argue that teachers are forced to resort to traditional teaching because pupils do not speak the language of instruction sufficiently (Alidou & Brock-Utne, 2011b;Hovens, 2002;Opoku-Amankwa, 2009). One of the reasons why, despite teachers' desire to use more interactive methods, the nature of interaction between the teacher and pupils was not changed may be the language barrier.…”
Section: Interaction With Pupilsmentioning
confidence: 73%
“…Considering the introduction of English at Standard Two, the researcher's impression was that teachers were required to implement policies or make curricular changes that had already been set by policy makers and deep collaborative and effective communication procedures were often overlooked. Hence, the decisions teachers of Standard Two made in the implementation process to effect the change from Setswana to English could affect learners' performance because they lacked appropriate skills and strategies to implement the changes required Johnson, 2010;Lin, 2006;Opoku-Amankwa, 2009). The situation is left fluid with minimal accountability on the risks and challenges teachers encounter regarding transition.…”
Section: Transition and Relevant Pedagogymentioning
confidence: 99%